Halford Mackinder a biography - Blouet, Brian W. (College Station Texas A&M University Press, 1987)
In the early twentieth century, Halford Mackinder established geography as a new discipline in English universities, predicted the decline of British influence in world affairs and the rise of European totalitarian regimes, and in his personal research made the first ascent of Mount Kenya. His views colored American foreign policy during World War II, and his far-reaching ideas--especially his "Heartland" theory--eventually had great influence on the way leaders of many nations thought about the world. Brian W. Blouet's vivid biography of this remarkable geopolitician describes the major phases of his life and the development of his thought, with a large segment devoted to Mackinder's prescient analyses of world affairs.
Includes index.
Keywords: Mackinder, Halford John, 1861-1947.